(untitled) (Intent Research Scientific Journal, 2024)
Hutchinson-Gilford progeria syndrome (HGPS) is an extremely rare hereditary fatal disease in newborn babies, HGPS is caused by mutations in LMNA that result in the production of an abnormal form of lamin A termed progerin. This genetic disease is very rare that the estimated incidence of HGPS in the USA is one in eight million births, based on the number of cases. Doctors and researchers say that the cause of death of these children is due to health problem, such as heart problem, veins and strokes. Doctors confirm that premature aging has nothing to do with the death of children with the rare disease (progeria). Currently, researchers and doctors are trying to understand premature aging and determine treatment options. Some areas of research include: Study genes and the course of disease to understand how it develops. This may help identify new treatments. Study of methods of preventing cardiovascular disease. Conducting human clinical trials with drugs that may be effective for treating premature aging. Testing other drugs to treat premature aging.